0

# When are the expressions 3x 12 and 3(x 4) equivalent Explain how you know?

Updated: 4/28/2022

Wiki User

8y ago

Best Answer

Expand the bracket.

Wiki User

8y ago
This answer is:

## Add your answer:

Earn +20 pts
Q: When are the expressions 3x 12 and 3(x 4) equivalent Explain how you know?
Write your answer...
Submit
Still have questions?
Related questions

12%6

0.75

### What is a expressions that simplifies to the same expression or value?

An equivalent expression.

### How can you use your knowledge of GCF and the distributive property to write equivalent expressions?

24 + 36 = (2 x 12) + (3 x 12) = 5 x 12 = 60

### Are the numeric expressions -3-(-9) and -9-3 equivalent?

No because -3-(-9) = 6 but -9-3 = -12

### Solve equivalent problems?

Explain why 49 -1/2 and -7 are not equivalent

### What expression is equivalent to x y 4x 3y 12?

This won't get answered successfully. There are no operational signs in the question and there are no following expressions to compare it to.

20

### Decide whether the two inequalities are equivalent. Explain. b and minus 12 and ge 4 b and le 16?

No, they are not equivalent.

### Definition for Equivalent Expressions?

Equivalent ExpressionDefinition of Equivalent ExpressionTwo algebraic expressions are said to be equivalent if their values obtained by substituting the values of the variables are same.More about Equivalent ExpressionTo symbolize equivalent expressions an equality (=) sign is used.Examples of Equivalent Expression3(x + 3) and 3x + 9 are equivalent expressions, because the value of both the expressions remains same for any value of x. For instance, for x = 4, 3(x + 3) = 3(4 + 3) = 21 and 3(x + 9) = 3 &times; 4 + 9( x + 3) = 21.The expressions 6(x2 + y + 2) and 6x2 + 6y + 12 are equivalent expressions and can also be written as 6(x2 + y + 2) = 6x2 + 6y + 12.Solved Example on Equivalent ExpressionChoose an expression that is equivalent to the expression 2n + 7(3 + n).Choices:A. 9n + 21B. -9n + 21C. -9n - 21D. n + 21Correct Answer: ASolution:Step 1: 2n + 7(3 + n) [Original expression.]Step 2: = 2n + 7(3) + 7(n) [Use the distributive property.]Step 3: = 2n + 21 + 7n [Multiply.]Step 4: = 2n + 7n + 21 [Use the commutative property.]Step 5: = 9n + 21 [Combine like terms.]well....in a totally inataquitly way...theotorical...e=mc2

### How you know that 7 12ths is greater than1 3rd but less than 2 3rds explain?

Equivalent fractions. 1/3 = 4/12 2/3 = 8/12 7 is greater than 4 but less than 8.

### What is an exspression?

Equivalent ExpressionDefinition of Equivalent ExpressionTwo algebraic expressions are said to be equivalent if their values obtained by substituting the values of the variables are same.More about Equivalent ExpressionTo symbolize equivalent expressions an equality (=) sign is used.Examples of Equivalent Expression3(x + 3) and 3x + 9 are equivalent expressions, because the value of both the expressions remains same for any value of x. For instance, for x = 4, 3(x + 3) = 3(4 + 3) = 21 and 3(x + 9) = 3 &Atilde;&mdash; 4 + 9( x + 3) = 21.The expressions 6(x2 + y + 2) and 6x2 + 6y + 12 are equivalent expressions and can also be written as 6(x2 + y + 2) = 6x2 + 6y + 12.Solved Example on Equivalent ExpressionChoose an expression that is equivalent to the expression 2n + 7(3 + n).Choices:A. 9n + 21B. -9n + 21C. -9n - 21D. n + 21Correct Answer: ASolution:Step 1: 2n + 7(3 + n) [Original expression.]Step 2: = 2n + 7(3) + 7(n) [Use the distributive Definition_for_Equivalent_Expressions.]Step 3: = 2n + 21 + 7n [Multiply.]Step 4: = 2n + 7n + 21 [Use the commutative property.]Step 5: = 9n + 21 [Combine like terms.]